Integrating Critical Literacy in the Middle School Classroom - Casey Medlock Paul (Middle Grades Review, 2016)
This article focuses on the integration of critical literacy in the middle school classroom. The author first explains critical literacy and the importance of incorporating it in the middle school curriculum. Then, a framework is presented in order to aid practitioners in implementing critical literacy instruction. Examples from relevant literature are presented as well, along with suggestions for how educators can begin teaching critical literacy and integrating it into their lessons.
Keywords: critical literacy; literacy; critical pedagogy; middle school